An inquiry into well-being and destitution - Dasgupta, Partha (Oxford : Clarendon, 1995)
Dealing comprehensively with the problem of poverty and undernourishment, this book addresses the debate over methods of estimating their incidence. It is an analytical and empirical inquiry into human well-being and the phenomenon of destitution as it occurs among rural populations of poor countries.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Poverty -- Developing countries; Income distribution -- Developing countries; Quality of life -- Developing countries; Developing countries -- Economic conditions